From financing needs to criminal terrorism: the role of terrorist financing in crime-terror relations - Marrero Rocha, Inmaculada C. (Oñati Socio-Legal Series, 2022)
After twenty years of national and international measures to combat financing of terrorism and money laundering, global terrorism has encountered greater restrictions to access the volume of economic resources it needs which has justified its collaboration with criminal organisations or conversion into criminal-terrorist organisations. This study seeks to analyse crime-terror relations by looking at the influence of the fight against terrorist financing in the evolution of global terrorist organisations, which have developed structures to establish a new range of relationships with transnational organised crime with unprecedented intensity. This article highlights some of the features that differentiate global terrorism from other types of terrorism, especially in terms of its objectives, organisational structures and funding possibilities, as well as pointing out a possible effect of the fight against terrorist financing in the relationship between terrorism and crime. Finally, it offers the different contexts where economic, political and social circumstances have created new cooperation models with organised crime groups.